3D-Printed Projectile Demonstrator and Its Implications on Students’ Conceptual Understanding and Attitudes toward Physics - Cabal, Marienne Sophia C.; Basagre, Rey-Mark G. (Schrödinger: Journal of Physics Education, 2025)
Purpose of the study: This study aimed to develop, evaluate, and implement a 3D-printed Projectile Demonstrator (3D-PPD) as an instructional tool for projectile motion, and analyze its implications on students’ conceptual understanding of projectile motion (CUPM) and attitudes toward physics (ATP).Methodology: The study employed a developmental and quasi-experimental research design. The 3D-PPD was designed using AutoCAD for 3D modeling and printed using a Bambu Lab X1 Carbon with AMS multicolor 3D printer. Research tools included survey and test questionnaires, an evaluation rating sheet, and a weekly learning plan. Statistical tests such as inferential statistics were performed using Jamovi software.Main Findings: The 3D-PPD received “very satisfactory” ratings in design (M = 3.62, SD = 0.27), instructional quality (M = 3.53, SD = 0.36), and cost-benefit (M = 3.40, SD = 0.38). It significantly improved students’ CUPM (p < 0.05, d = 0.90) but showed no significant improvement in ATP (p = 0.294, d = 0.43). Furthermore, the correlation analysis between CUPM and ATP after exposure to the 3D-PPD yielded a p-value of 0.818, indicating a statistically insignificant relationship.Novelty/Originality of this study: This study pioneers the development of an instructional tool through 3D printing, recognizing how modern fabrication technologies can concretize abstract physics concepts and offer scalable solutions to instructional material gaps in physics education. It also offers a significant insight into distinct students’ learning dimensions which emphasizes the need for contextualized support to inform future instructional design and research.